A new scarab species, Aphodius gissaricus (Coleoptera: Scarabaeidae: Aphodiinae), from the Pamir-Alay Mountains in Tajikistan - Akhmetova, Lilia; Frolov, Andrey (Zootaxa, 2012)
The fauna of the aphodiines of Pamir-Alay Mountains is relatively well known and is not very rich in comparison to the adjacent territories of lowland Middle Asia (Medvedev & Lopatin 1961, Protsenko 1968, Nikolajev 1987). For example, some 30 species of Aphodius Hellwig are known from Tajikistan (Medvedev & Lopatin 1961) and most of them are widely distributed in Irano-Turanian biogeographic region and in the Palaearctic. However endemism is rather high: none of these species occur outside the Palaearctic (except for recent introductions of a few species to the Nearctic and Australian Realms) and many are limited to deserts or single mountain systems.